2007
DOI: 10.1103/physrevb.75.214203
|View full text |Cite
|
Sign up to set email alerts
|

Nonsaturating magnetoresistance of inhomogeneous conductors: Comparison of experiment and simulation

Abstract: The silver chalcogenides provide a striking example of the benefits of imperfection. Nanothreads of excess silver cause distortions in the current flow that yield a linear and nonsaturating transverse magnetoresistance ͑MR͒. Associated with the large and positive MR is a negative longitudinal MR. The longitudinal MR only occurs in the three-dimensional limit and thereby permits the determination of a characteristic length scale set by the spatial inhomogeneity. We find that this fundamental inhomogeneity lengt… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
108
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(112 citation statements)
references
References 29 publications
3
108
0
1
Order By: Relevance
“…Поле кроссовера B c уменьшалось при понижении температуры, т. е. линей-ный вклад в общую зависимость MR(B) постепенно возрастал. Линейное положительное магнитосопротивление в металлах и полупроводниках может быть обусловлено несколькими механизмами [10][11][12][13]. Один из механизмов развит для структурно неоднородных и неупорядочен-ных полупроводников [12,13].…”
Section: международная конференция "unclassified
“…Поле кроссовера B c уменьшалось при понижении температуры, т. е. линей-ный вклад в общую зависимость MR(B) постепенно возрастал. Линейное положительное магнитосопротивление в металлах и полупроводниках может быть обусловлено несколькими механизмами [10][11][12][13]. Один из механизмов развит для структурно неоднородных и неупорядочен-ных полупроводников [12,13].…”
Section: международная конференция "unclassified
“…6 The explanation of the non-saturating properties of MR can be based on the large spatial fluctuations in the conductivity of the narrow-gap semiconductors, due to the inhomogeneous distribution of silver ions. 7,8 It has been also shown that the large positive MR is induced by the quasi-neutrality breaking of the space-charge effect in Si. 9 The large positive MR has been also reported by Schoonus et al in Boron-doped Si-SiO 2 -Al structures.…”
Section: Introductionmentioning
confidence: 99%
“…Several mechanisms have been suggested to explain this behavior from geometrical [22], classical [23][24][25], quantum [26,27], and effective medium [28,29] perspectives.…”
Section: Introductionmentioning
confidence: 99%